India's outward foreign direct investment: emerging trends and issues. Issue 1 (2nd January 2018) - Iqbal, Badar Alam; Turay, Abdul; Hasan, Munir; Yusuf, Nadia
Abstract: India is an increasingly attractive destination for foreign investments, and the country is also becoming a significant source of outward foreign investments. The increasing engagement of the Indian corporations in the world markets is an indication of the maturity reached by Indian industries as well as the extent of their participation in an overall globalization process. Indian firms invest across a wide variety of sectors and countries, departing from trading and textiles in developing countries, which has been their major investment focuses. This paper studies Indian outward foreign direct investment (OFDI). Its main highlights are to examine the global and Indian trends in OFDI in the recent years, analyze the sector- and country-wide OFDI from India, and investigate global acquisitions by Indian corporations and their destinations. The analysis shows that Indian OFDI is the highest in Mauritius and Singapore and the least in Hong Kong and Switzerland. By sectors, the highest overseas investments were made in the financial and business services in 2010 and 2011.